An alarmingly high nasal carriage rate of Streptococcus pneumoniae serotype 19F non-susceptible to multiple beta-lactam antimicrobials among Vietnamese children - Hien Anh Thi Nguyen; Hiroshi Fujii; Huong Thi Thu Vu; Christopher M. Parry; Anh Duc Dang; Koya Ariyoshi; Lay-Myint Yoshida (BMC Infectious Diseases, 2019)
Abstract Background Understanding the relationship between serotype epidemiology and antimicrobial susceptibility of Streptococcus pneumoniae is essential for the effective introduction of pneumococcal conjugate vaccines (PCVs) and control of antimicrobial-resistant pneumococci. Methods We conducted a community-based study in Nha Trang, central Vietnam, to clarify the serotype distribution and pattern of S. pneumoniae antimicrobial susceptibility in children under 5 years of age and to identify risk factors for carrying antimicrobial-resistant strains. Nasopharyngeal swabs collected from children with acute respiratory infections (ARIs) hospitalized between April 7, 2008, and March 30, 2009, and from healthy children randomly selected in July 2008 were subjected to bacterial culture. Minimum inhibitory concentrations (MICs) against S. pneumoniae were determined, and multiplex-polymerase chain reaction (PCR) serotyping assays were performed. Logistic regression was applied to identify risk factors. Results We collected 883 samples from 331 healthy children and 552 ARI cases; S. pneumoniae was isolated from 95 (28.7%) healthy children and 202 (36.6%) ARI cases. Age and daycare attendance were significantly associated with pneumococcal carriage. In total, 18.0, 25.8 and 75.6% of the isolates had high MICs for penicillin (≥4 μg/ml), cefotaxime (≥2 μg/ml) and meropenem (≥0.5 μg/ml), respectively. The presence of pneumococci non-susceptible to multiple beta-lactams was significantly associated with serotype 19F (Odds Ratio: 4.23) and daycare attendance (Odds Ratio: 2.56) but not ARIs, age or prior antimicrobial use. The majority of isolates non-susceptible to multiple beta-lactams (90%) were PCV13 vaccine serotypes. Conclusions S. pneumoniae serotype 19F isolates non-susceptible to multiple beta-lactams are widely prevalent among Vietnamese children. Vaccine introduction is expected to significantly increase drug susceptibility.